A systematic review of the so-called cosmopolitan polydorid Polydora hoplura Claparede, 1869 (Polychaeta: Spionidae) on the South African coast. - Van Niekerk, Sandy Eve (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.